9th surgery decoction alleviates psoriasis-like inflammation through the downregulation of angiogenesis induced by HIF-1α and the EGFR-PI3K-AKT-mTOR pathways - Shengjie Zhu; Xinyi Feng; Ge Yan; Xin Liu; Yuanran Chen; Likun Zhang; Kan Ze (Phytomedicine Plus)
Background: 9th Surgery Decoction (9SD) is a long clinically-proved herbal mixture against inflammatory skin diseases like psoriasis, eczema and acne. There still lacks researches revealing the role of 9SD in treatment of psoriasis. This work investigated the mechanism of 9SD in psoriasis treatment. Methods: The main components of the 9SD were analyzed using ultra-high performance liquid chromatography with quadrupole time-of-flight mass spectrometry. Network pharmacology was employed to identify potential targets and pathways. Psoriasis-like inflammation was induced in human keratinocytes and human umbilical vein endothelial cells using a cytokine cocktail, and the therapeutic effects of the decoction were validated in vitro. Imiquimod-induced psoriasis-like dermatitis in mice was used to assess the effects in vivo. Histopathological changes, gene expression, and protein levels were analyzed using various techniques, including real-time quantitative polymerase chain reaction, enzyme-linked immunosorbent assay, and western blotting. Results: The study revealed that 9SD contains multiple active components that target various pathways involved in psoriasis. It was found to exert anti-inflammatory effects by reducing the levels of cytokines such as epidermal growth factor, vascular endothelial growth factor, and tumor necrosis factor-alpha. Additionally, the decoction inhibited angiogenesis by downregulating hypoxia-induced factor 1-alpha and the epidermal growth factor receptor-phosphoinositide 3-kinase-protein kinase B-mechanistic target of rapamycin signaling pathways. Conclusions: The 9SD demonstrates significant anti-psoriatic effects by targeting inflammation and angiogenesis through multiple pathways. These findings suggest that the decoction could be a promising therapeutic option for psoriasis, particularly in modulating the vascular and inflammatory aspects of the disease.